Mechanism of malignant hypercalcaemia in carcinoma of the breast. Issue 6498 (21st September 1985) - Percival, R C; Yates, A J; Gray, R E; Galloway, J; Rogers, K; Neal, F E; Kanis, J A
Abstract : To investigate the mechanisms of hypercalcaemia in carcinoma of the breast, 22 patients with hypercalcaemia due to metastatic carcinoma were studied and the findings compared with those obtained in normal subjects and patients with benign and malignant breast disease without hypercalcaemia. As expected, patients with metastases of bone showed biochemical evidence of increased bone resorption. Whereas all patients with hypercalcaemia had skeletal metastases, not all patients with skeletal metastases had hypercalcaemia despite considerable degrees of bone resorption. The presence of hypercalcaemia was associated with a significant increase in renal tubular reabsorption of calcium (p less than 0.001) and decreased reabsorption of phosphate (p less than 0.001) despite adequate rehydration of patients. These studies suggest that increased renal tubular reabsorption of calcium, possibly mediated by a humoral factor with activity similar to that of parathyroid hormone, contributes appreciably to the hypercalcaemia of malignant breast disease.